2009
DOI: 10.1021/jp902547d
|View full text |Cite
|
Sign up to set email alerts
|

Tetra-n-butylammonium Borohydride Semiclathrate: A Hybrid Material for Hydrogen Storage

Abstract: In this study, we demonstrate that tetra-n-butylammonium borohydride [(n-C(4)H(9))(4)NBH(4)] can be used to form a hybrid hydrogen storage material. Powder X-ray diffraction measurements verify the formation of tetra-n-butylammonium borohydride semiclathrate, while Raman spectroscopic and direct gas release measurements confirm the storage of molecular hydrogen within the vacant cavities. Subsequent to clathrate decomposition and the release of physically bound H(2), additional hydrogen was produced from the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 40 publications
0
37
2
2
Order By: Relevance
“…It is generally known that hydrates have several properties, such as high gas-storage capacity, large heat of formation and decomposition, and guest substance selectivity. These properties enable hydrates to be applied to various industrial technologies, for example, transportation and storage of natural gas and hydrogen [3][4][5][6], the ocean and ground sequestration of CO 2 [7][8][9] , developing highly efficient heat pump and refrigeration [10], and gas separation [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally known that hydrates have several properties, such as high gas-storage capacity, large heat of formation and decomposition, and guest substance selectivity. These properties enable hydrates to be applied to various industrial technologies, for example, transportation and storage of natural gas and hydrogen [3][4][5][6], the ocean and ground sequestration of CO 2 [7][8][9] , developing highly efficient heat pump and refrigeration [10], and gas separation [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the following dissociation temperatures have been reported in ascending order of size: T = 301 K for TBAF and TBA hydroxide hydrates [7,14,15], T = 288 K for TBA chloride (TBAC) hydrate [3,11], and T = $286 K for TBAB hydrate [9][10][11]. Such semiclathrate hydrates can be stable at temperatures between T = (273 and 300) K, and are capable of trapping small gas molecules (e.g., H 2 , CH 4 , CO 2 , and N 2 ) under milder conditions than those required for the corresponding pure gas hydrate (e.g., [16] storage materials have been carried out by many research groups (e.g., [16][17][18][19][20][21][22][23][24][25]). In particular, fundamental and applied studies on TBAB hydrates have been conducted in detail because of the relatively noncorrosive nature of this hydrate system.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 hydrate has a type-II structure in the pressure range of 0.18 to 0.22 GPa at a temperature of 249 K [5]. It was recently found that the addition of a second guest substance, such as tetrahydrofuran (THF) [6][7][8][9][10], quaternary ammonium salts [8,11,12], cyclohexanone [13] or amines [14] is effective in lowering the stability pressure. However, this technique is still highly discussed because the addition of second guests reduces the overall H 2 storage capacity.…”
Section: Introductionmentioning
confidence: 99%